(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Non-traumatic myelopathies has several etiologies. Objectives: The aim of the study was to see the etiology of non-traumatic myelopathy based on magnetic resonance imaging (MRI) changes in the context of Bangladesh. Methodology: Patients clinically diagnosed as non-traumatic myelopathy in the department of neurology of Sir Salimullah Medical College and Hospital (SSMCH), and in the inpatient wards of the National Institute of Neurosciences (NINS), considering the inclusion and exclusion criteria were enrolled as the study population from May 2014 to December 2015. Age, gender, clinical presentations and type of lesion based on MRI changes were collected. All the data were analyzed statistically. Results: Total 100 cases satisfied the inclusion and exclusion criteria in this study. Among them, there were 62 males and 38 females with a male to female ratio of 1.63:1. The mean age was found to be (mean ± SD) 45.80 ±15.28 with age ranges from 15 to 74 years. The highest number of patients (26.0%) was in the age group 51-60 years, followed by 24% patients in the age group 31-40 years. Based on MRI scan, most common etiologies that commonly diagnosed are cervical spondylotic myelopathy (31%), transverse myelitis (26%), primary spinal tumour (13%), spinal tuberculosis(12%), spinal metastatic disease (12%), and unclassified (6%). MRI scan also detect the common sites of involvements of these causes. Conclusion: In this study cervical spondylotic myelopathy, transverse myelitis, and spinal tuberculosis are the most common cause of non-traumatic myelopathy in the context of Bangladesh. Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 87-91